8. Motivasi Kerja Terhadap Produktivitas Kerja Pegawai Dinas Perhubungan Provinsi Nusa Tenggara Barat Di Bidang Udara - Vidyana Mandrawaty (Sekolah Tinggi Teknologi Kedirgantaraan, 2018)
This study aims to determine the effect of work motivation on the work productivity of West Nusa Tenggara Province Transportation Department employees in the air sector. The population in this study were employees who worked in the air field at the West Nusa Tenggara Provincial Transportation Department with a total of 25 employees. This research is a quantitative study conducted by distributing questionnaires to 25 respondents and doing documentation, and processing data using SPSS 16.0 Windows application. Based on the results of the study indicate that work motivation has a significant effect on the work productivity of the West Nusa Tenggara Provincial Transportation Department employee in the air sector Agustus 2018 and has an influence of 40%, the remaining 60% is influenced by other variables not examined in this study.